Social Distancing Effect on Workspace Nature and HRM: Evidence from Egypt and GCC - Wagdi, Osama; Abouzeid, Walid (The journal of contemporary issues in business and government, 2021)
This study investigates the practices of human resources management (HRM) in Egypt and the Gulf Cooperation Council through the integration of quantitative data (social distancing in the workplace) and qualitative data (attitude toward altering the workplaces nature and human resources practices) using a survey of 140 HRM personnel from seven nations. The study found that social distancing explains 54% of the change in workplace nature, while social distancing and the change in workplaces nature explain 32% of the change in HRM practices. However, there is a distinction in the extent to which the characteristics of job location have changed, as the number of people is a variable for HRM practices due to COVID-19, with training needs and training tools changing the most during the COVID-19 pandemic.